Public management and governance in Malaysia : trends and transformations - Siddiquee, Noore Alam. (Milton Park, Abingdon, Oxon ; New York, N.Y. : Routledge, 2013)
'The past two and a half decades have seen major transformations in public sector management and governance across the globe. This book examines the ways public sector management and governance in Malaysia has changed and is changing under contemporary reform models. Chapters are written by well-established scholars and academics with intimate knowledge in their respective fields, and provide a thorough and insightful analysis of the reform trends and developments on a range of topics. These include performance management, compensation reforms, public budgeting, accounting and reporting, privatisation and public-private partnership, e-government, managing ethics and accountability, local government and inter-governmental relations. While the book surveys the topics that are central to public sector management and governance, it also focuses on the nature of reforms and changes that were introduced, as well as the forces that have shaped their design and implementation process, and the initial impacts and results'--
1. Introduction / Noore Alam Siddiquee -- 2. The public bureaucracy : an analytical overview / Noore Alam Siddiquee -- 3. Managing people : strategic human resource management initiatives in the public service / John Antony Xavier -- 4. Managing for excellence : performance management in the public service / John Antony Xavier -- 5. Pay for performance : compensation reforms / Norhaslinda Jamaludin -- 6. Financial administration I : government budgeting / Nor Azlina Ariffin -- 7. Financial administration II : accounting and reporting / Zakiah Saleh -- 8. Redefining relationships : privatisation and public-private partnerships / Kuppusamy Singaravelloo -- 9. Electronic government : developments and trends / Maniam Kaliannan, Murali Raman and Magiswary Dorasamy -- 10. Managing ethics : drives for fighting corruption and enhancing integrity / Noore Alam Siddiquee --11. Local government and inter-governmental relations / Kuppusamy Singaravelloo -- 12. Development planning and policy : the NEM in perspective / Syed Serajul Islam -- 13. Environment policy and governance / Abdul Raufu Ambali -- 14. Conclusion / Noore Alam Siddiquee.
Keywords: Public administration -- Malaysia; Malaysia -- Politics and government